22q11.2 DELETION SYNDROME: ALGORITHM FOR THE EARLY DIAGNOSIS AND TREATMENT - Leyla S. Namazova-Baranova; Olga V. Ginter; Tatyana A. Polunina; Irina V. Davydova; Kirill V. Savostyanov; Alexandr A. Pushkov; Natalya V. Jourkova; Tatyana Y. Mospan (Вопросы современной педиатрии)
Chromosomal diseases, in particular microdeletions, determine the child's condition as well as the prognosis for a disease even at birth. With timely identified chromosomal abnormalities, we can diagnose not only obvious but also hidden disorders in the organs and their systems and timely correct the child's treatment at an early age. The algorithm for diagnosis of chromosomal abnormalities in children is an important component of a modern pediatric practice. It allows to increase the effectiveness of chromosomal pathology treatment.